Transgenic foods associated with the development of diseases: a literature review (Research, Society and Development, 2022)
The present study approaches the problem of transgenic foods or also called genetically modified foods. Data were obtained through a bibliographic review of selected articles related to the subject of interest, in Google Scholar, Scielo, Biblioteca Virtual and Jornal Brazilinam Journal, published in recent years in Portuguese. In the national scenario, Brazil occupies the 2nd place in the world ranking in production and consumption of transgenics. The technique aims to manipulate the DNA, in some cases using the insertion of genetic material from different species of the organism to be modified, in order to improve some aspects of the plants, for example, resistance to pests, increase in nutritional value, resistance to variations in humidity, temperature, aiming mainly to increase the productions. In Brazil, 90% of the corn and 92% of the soy produced are genetically modified. Despite the scientifically proven benefits, it is essential to correlate these data with research showing some possible losses of the technique, mostly related to environmental, human and animal health problems. Another point to be analyzed concerns the little information available on genetically modified organisms, making it difficult for consumers to know and accept them and to guarantee safety by the scientific community.